Menginvestigasi Masalah yang Dihadapi Pelajar Ekstrovert dalam Penampilan Berbicara - Syarafina, Danti Fadiah; Santoso, Dian Rahma (Indonesian Journal Publisher, 2024)
This study conducted with the aim to find out the tendency of issues faced by learners in speaking performance and find out how well learners do in speaking performance. This study is a descriptive qualitative study that used the ‘Big Five Personality Traits’ to determine students' personality. The information about the issues faced by the learners gained from questionnaire, interview, observation, and speaking test. Extrovert personality is determined from the aspects of cognition and behavior which are the core of each individual's structure. There were 18 students indicated as extroverts. The result of this study explained that there were some issues faced by extroverted learners in linguistics factor that became the main factor. The most influential factors for speaking success were learners’ readiness and managing better strategy for speaking, built an immersive speaking activities approach, being open about new topics, and gave encouraging and supportive feedback to each other.